The interplay of DNA methyltransferases and demethylases with tuberization genes in potato (Solanum tuberosum L.) genotypes under high temperature - Dutta, Madhushree; Raturi, Vidhi; Gahlaut, Vijay; Kumar, Akhil; Sharma, Paras; Verma, Vipasha; Gupta, Vijai Kishor; Sood, Salej; Zinta, Gaurav (Frontiers in Plant Science, 2022)
Potato is a temperate crop consumed globally as a staple food. High temperature negatively impacts the tuberization process, eventually affecting crop yield. DNA methylation plays an important role in various developmental and physiological processes in plants. It is a conserved epigenetic mark determined by the dynamic concurrent action of cytosine-5 DNA methyltransferases (C5-MTases) and demethylases (DeMets). However, little is known about the expression patterns of C5-MTase and DeMets under high temperatures in potato. Here, we performed genome-wide analysis and identified ten C5-MTases and eight DeMets in potato. Analysis of their conserved motifs, gene structures, and phylogenetic analysis grouped C5-MTases into four subfamilies (StMET, StCMT3, StDRM, StDNMT2), and DeMets into three subfamilies (StROS, StDML, StDME). Promoter analysis showed the presence of multiple cis-regulatory elements involved in plant development, hormone and stress response. Furthermore, expression dynamics of C5-MTases and DeMets were determined in the different tissues (leaf, flower and stolon) of heat sensitive (HS) and heat tolerant (HT) genotypes under high temperature. qPCR results revealed that high temperature resulted in pronounced upregulation of CMT and DRM genes in the HT genotype. Likewise, demethylases showed strong upregulation in HT genotype as compared to HS genotype. Several positive (StSP6A, StBEL5) and negative (StSP5G, StSUT4 and StRAP1) regulators are involved in the potato tuberization. Expression analysis of these genes revealed that high temperature induces the expression of positive regulators in the leaf and stolon samples of HT genotype, possibly through active DNA demethylation and RNA-directed DNA methylation (RdDM) pathway components. Our findings lay a framework for understanding how epigenetic pathways synergistically or antagonistically regulate the tuberization process under high-temperature stress in potato. Uncovering such mechanisms will contribute to potato breeding for developing thermotolerant potato varieties.